DEVELOPMENT OF ANDROID-BASED LEARNING MEDIA FOR CLASS XI IPA MAN 4 BANJAR COLOID SYSTEM MATERIALS - Amaliah, Nor; Kartika Irawati, Ratna; Haitami, Iqbal (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2022)
This study aims to determine the validity of the development of android-based learning media on colloid system material for Class XI IPA MAN 4 Banjar, and to determine student responses to the development of android-based learning media on colloid system material for Class XI IPA MAN 4 Banjar. The type of research used in this research is Research and Development (R & D). The development model used in this study is the ADDIE model, namely the research stages of Analysis, Design, Development and Product Manufacturing, Implementation, and Evaluation. However, in this study the evaluation stage was not carried out. The subjects of this study were students of Class XI Science at MAN 4 Banjar in the 2021/2022 academic year. The learning media developed were based on the results of the assessment of media experts, material experts, subject teachers and students' responses to the development of android-based learning media. The results of this study show the following: the validity level of android-based learning media products on colloidal system material gets a validity level percentage of 79% with a valid category, media experts' assessments get a validity level percentage of 95% with a very valid category, assessment from subject teachers Chemistry class XI MAN 4 Banjar gets a percentage of 85% in the valid category, and students' responses to Android-based learning media for field trials get an assessment percentage of 89% in the very practical category.